Recent growth in African cassava - Nweke, Felix I.; Haggblade, Steven; Zulu, Ballard (International Food Policy Research Institute, 2004)
According to the authors, Cassava serves as a staple food for 200 million Africans, second only to maize in its calorie contribution. In response to a series of devastating attacks by cassava diseases and pests over the past several decades, the International Institute of Tropical Agriculture (IITA) and several national agricultural research services have launched successful cassava research programs... " This brief describes some of the programs, their impact and the drivers of change. It concludes with an analyis of the key lessons learned for building future successes.